2021
DOI: 10.1186/s13044-021-00095-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between thyroid autoimmunity and ovarian reserve in women with hypothyroidism

Abstract: Background The ovarian function and therefore the ovarian reserve may be compromised by the pathogenesis of autoimmune diseases of which, Hashimoto’s thyroiditis (HT) is the most common in women of reproductive age. Furthermore, a prolonged reduction in thyroid hormone concentration results in a broad spectrum of reproductive alteration. Previous reports in the literature have been controversial regarding the impact of hypothyroidism and alterations in the ovarian reserve. Thus, this prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
(38 reference statements)
0
13
0
Order By: Relevance
“…Adamska et al [20] also reported a negative correlation between serum AMH and the percentage of body fat mass, as estimated by bioimpedance analysis, in a group of 39 women with Hashimoto's thyroiditis, but not in 46 control women. By contrast, no correlation between AMH and BMI was observed in two older studies [11,18]. Recently, AMH was evaluated in women with polycystic ovarian syndrome, and was found to be significantly and negatively correlated with BMI and waist-to-height ratio [28].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Adamska et al [20] also reported a negative correlation between serum AMH and the percentage of body fat mass, as estimated by bioimpedance analysis, in a group of 39 women with Hashimoto's thyroiditis, but not in 46 control women. By contrast, no correlation between AMH and BMI was observed in two older studies [11,18]. Recently, AMH was evaluated in women with polycystic ovarian syndrome, and was found to be significantly and negatively correlated with BMI and waist-to-height ratio [28].…”
Section: Discussionmentioning
confidence: 93%
“…A literature search conducted at the end of 2021 identified several papers in which AMH and thyroid function and/or autoimmunity were evaluated. The studies involved had mainly been conducted in centres for human reproduction, and no agreement emerged on the role of the thyroid in AMH secretion or indirectly on the ovarian reserve [11][12][13][14][15][16][17][18][19][20][21]. In 2015, a study involving a large number of women undergoing screening for infertility, in which a cross-sectional retrospective analysis of AMH, free-thyroxine (f-T4), TSH and thyroperoxidase antibody (TPOAb) was conducted, concluded that thyroid autoimmunity and function were not associated with low ovarian reserve [12].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, enhanced glycolysis may increase recruitment from the primordial follicle pool, resulting in a higher density of small preantral follicles in PCOS patients. POI is not only induced by genetic and iatrogenic factors but is also associated with autoimmune conditions, such as hypothyroidism [ 40 , 41 ] and diabetes [ 42 ]. It has been reported that a downregulated lncRNA-ALDOA in granulosa cells and the gene variant of HK3 are associated with POI [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been determined that hypothyroidism, which is common in autoimmune thyroid disease, also affects the menstrual cycle. Although some studies argue that women with hypothyroidism commonly experience oligomenorrhea during the menstrual cycle, some claim the opposite (17,18) Studies have shown that hypothyroidism is significantly higher in women with low ovarian reserve due to genetic reasons. According to the results of one study, approximately half of women with low ovarian reserve due to Turner syndrome have subclinical hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%